ADVANTAGES AND DISADVANTAGES OF DISTANCE LEARNING FOR LANGUAGES IN MEDICAL UNIVERSITIES IN A PANDEMIC SITUATION - Xalmuratova M. T. (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The requirements for the quality of language training of non-linguistic specialists, and in particular, future clinicians, that have increased in recent years, have led to corresponding transformations, both in the forms of organizing the educational process and in the use of various methods, teaching aids and forms of control in medical universities. Today, knowledge of a foreign language is not a luxury, as it once was, but a vital necessity. Learning a foreign language in the modern world is one of the most important moments in the life of a modern, successful person. A foreign language is necessary not only to effectively interact in science and politics, culture and art, economics, but also in medicine and other important areas of our life. One of the conditions for the professional competence of a future doctor is knowledge of a foreign language. The study of a foreign language in medical universities is considered as an obligatory component of the professional training of a specialist. Knowledge of a foreign language makes it possible for a future doctor to improve his qualifications, to practice abroad, in order to exchange experience and knowledge with foreign colleagues, to participate in international conferences, seminars, webinars. Knowing a foreign language, a medical student can study various medical literature, visit websites, write scientific articles, conduct research in foreign languages, conduct conversations using medical terms, compose and translate medical documentation describing diseases, choose possible methods, methods of treating a disease, procedures, drugs, manipulations, etc. In addition to all this, knowledge of a foreign language is also important in communicating with patients, native speakers.